Chromogranin a staining as a prognostic variable in newly diagnosed Gleason score 7–10 prostate cancer treated with definitive radiotherapy. Issue 5 (30th December 2013) - Krauss, Daniel J.; Amin, Mitual; Stone, Brandon; Ye, Hong; Hayek, Sylvia; Cotant, Matthew; Hafron, Jason; Brabbins, Donald S.
Abstract PURPOSE To demonstrate the association of neuroendocrine differentiation, as identified by chromogranin A (CgA) staining, with clinical outcomes in newly diagnosed prostatic adenocarcinoma treated with definitive radiotherapy (RT). MATERIALS/METHODS Patients with Gleason score ≥7 adenocarcinoma were identified from our outcomes database. RT consisted of external beam, brachytherapy, or external beam with brachytherapy boost. Biopsy specimens were stained for neuroendocrine differentiation with CgA. Results were interpreted by a single pathologist. CgA staining was quantified as 0%, <1%, 1–10%, or >10% of tumor cells. Clinical outcomes were blinded at the time of pathologic evaluation. RESULTS CgA staining was performed on 289 patients. 149 patients had Gleason score 7, and 140 were Gleason score 8–10. Median follow‐up was 6.5 years. For patients with <1% versus >1% CgA staining, pretreatment characteristics were well‐balanced. CgA staining was detected in 90 cases (31%). 58 patients had focal positive (<1%) CgA staining, and 32 cases had >1% of tumor cells CgA positive. Patients with >1% CgA staining had inferior biochemical control, clinical failure, distant metastases (DM), and cause‐specific survival (CSS) rates. Ten‐year rates of DM were 8% versus 48% for patients with <1% versus >1% CgA positive cells, respectively (P < 0.001). CSS at 10 years was 95% versus 76%, respectively (P < 0.001). Local control was equivalent in the two patient cohorts. Patients with <1% CgA staining had similar outcomes to those patients with 0% staining. CONCLUSIONS Neuroendocrine differentiation involving >1% of tumor cells on prostate cancer biopsies is a predictor of DM and CSS in patients treated with primary RT. Prostate 74:520–527, 2014. © 2013 Wiley Periodicals, Inc.